AI-Driven Diagnostics and Imaging: Transforming Early Detection and Precision in Healthcare - Sriram Sitaraman (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Artificial intelligence is revolutionizing medical imaging and diagnostics, marking a transformative era in healthcare delivery. This comprehensive article explores the evolution from early computer-aided diagnosis systems to sophisticated deep-learning architectures, examining their impact across radiology, pathology, and clinical workflows. The article covers breakthrough technologies, including vision transformers, multi-modal integration, and explainable AI frameworks, highlighting their contributions to improved diagnostic accuracy and efficiency. The article encompasses the clinical benefits of early disease detection, workflow optimization, and cost reduction while addressing crucial challenges in regulatory compliance, ethical considerations, and data privacy. Looking ahead, the review examines emerging trends in federated learning, infrastructure requirements, and the economic implications of AI implementation in healthcare settings, providing insights into the future landscape of AI-driven medical imaging.